2020
DOI: 10.30994/sjik.v9i2.404
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Birthing Ball Therapy On The Duration Of The First Stage Of Labor And The Intensity Of Labor Pain In Primigravid Mothers Giving Births

Abstract: This type of research is an observational analytic study with a cross-sectional design. The sampling technique used Simple Random Sampling. The sample size was 40 mothers with the division of 20 mothers used birthing ball therapy and 20 mothers did not use birthing ball therapy. Data collection tools were observation sheets. Data analysis was performed using Chi-Square and Multiple Logistic Regression analysis. There was a positive effect of using the Birth Ball with the duration of the first stage of labor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Apart from that, feeling relaxed can also help the mother in labor to be more sensitive to uterine contractions, thereby increasing the effectiveness of contractions. 9,10 The birthing process is a natural process, but it can be a tiring and painful process for the birth mother.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, feeling relaxed can also help the mother in labor to be more sensitive to uterine contractions, thereby increasing the effectiveness of contractions. 9,10 The birthing process is a natural process, but it can be a tiring and painful process for the birth mother.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review on the effects of maternal movement during labor found that it can cause decreased pain, facilitate maternal-fetal circulation, increase the intensity of uterine contractions, reduce labor duration, aid in descent and station of the presenting part of the fetus and decrease rates of perineal trauma and episiotomy. In this context, the use of birth balls allows women to take different positions (Suryani & Hardika, 2020).…”
Section: The Difference In the Decrease In The Level Of Pain In The F...mentioning
confidence: 99%
“…Suryani et al, en 2020, determinaron un efecto positivo en la intensidad del dolor en primigrávidas al usar la bola de parto (OR =7,57; IC 95 %; 1,53 a 37,3; p =0,013), el cual fue estadísticamente significativo. Demostraron que el uso de una bola de parto es eficaz para acortar la primera etapa del trabajo de parto y reducir la intensidad del dolor 33 .…”
Section: Influencia De La Terapia De Balón En El Alivio Del Dolorunclassified